Novel Sample-Stage for Combined Near Ambient Pressure X-ray Photoelectron Spectroscopy, Catalytic Characterization and Electrochemical Impedance Spectroscopy - Raffael Rameshan (Crystals, 2020)
For an in-depth characterization of catalytic materials and their properties, spectroscopic in-situ (operando) investigations are indispensable. With the rapid development of advanced commercial spectroscopic equipment, it is possible to combine complementary methods in a single system. This allows for simultaneously gaining insights into surface and bulk properties of functional oxides, such as defect chemistry, catalytic characteristics, electronic structure, etc., enabling a direct correlation of structure and reactivity of catalyst materials, thus facilitating effective catalyst development. Here, we present a novel sample-stage, which was specifically developed to pave the way to a lab–based combination of near ambient pressure X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy with simultaneous catalytic operando measurements. This setup is designed to probe different (model) systems under conditions close to real heterogeneous catalysis, with a focus on solid oxide electrochemical cells. In a proof of concept experiment using an electrochemical model cell with the doped perovskite Nd0.6Ca0.4Fe0.9Co0.1O3-δ as working electrode, the precise control of the surface chemistry that is possible with this setup is demonstrated. The exsolution behavior of the material was studied, showing that at a lower temperature (500 °C) with lower reducing potential of the gas phase, only cobalt was exsolved, forming metallic particles on the surface of the perovskite-type oxide. Only when the temperature was increased to 600 °C and a cathodic potential was applied (−250 mV) Fe also started to be released from the perovskite lattice.